Sosialisasi dan pelatihan pembuatan e-magazine dalam pembelajaran kimia di SMA Negeri Pintar Provinsi Riau - Tri Padila Rahmasari; Lani Dwi Kurnia; Gesty Mika Juwani; Adek Diah Murti; Khairu Anugrah Perdana Putra; Roza Linda (Unri Conference Series: Community Engagement, 2019)
One of the problems in education is educators have not been able to prepare innovative teaching materials in accordance with the progress and development of science and technology. Educators are required to provide innovations to increase students' interest in learning, especially in industrial revolution 4.0. This activity aims to provide understanding and skills to students and teachers in using electronic-based teaching materials and training of e-magazine making in chemistry learning. The activity was carried out in SMAN Pintar which is located in Taluk Kuantan. SMAN Pintar is a boarding school that has adequate infrastructure and facilities, it requires optimization of science and technology, because of that this school can participate in the 4.0 industrial revolution. The method of implementing this program is the provision of material in socialization about 21st-century learning and the use of e-magazine as companion teaching materials, followed by training teachers in making e-magazine using Kvisoft Flipbook Maker application. The results of this program are e-magazine products, usage manuals, and program review books. The evaluation of the program is follow-up by giving a post-test questionnaire and a final review of the program book. This activity received a positive response from students and teachers of SMAN Pintar, Riau Province.